Prevalence of Cigarette Smoking and its Characteristics among Undergraduate Medical Students at AL-Ghad International College, Abha City, Saudi Arabia - Omer Yahia, Amar Ibrahim; Alshahrani, Saad Abdullah Saad; Asiri, Hani Ali Mohammed (Indian Journal of Community Health, 2018)
Background: Cigarette smoking among medical students is becoming a serious public health problem worldwide. Objectives: To determine the daily cigarette smoking prevalence and its characteristics among undergraduate medical students at AL-Ghad International College, Abha city, Saudi Arabia. Methods and Materials: A community based cross-sectional study was conducted at AL-Ghad International College, Abha city, Saudi Arabia. A validated self-administered questionnaire was used to collect data from the participants. Descriptive data analysis was performed using Statistical Package for the Social Sciences (SPSS) version 17. Association between different variables was performed using Chi-square and ANOVA tests. A P-value of less than 0.05 was considered statistically significant. Results: The prevalence of daily cigarette smoking was 30.25%. Significant associations were found between the cigarette smoking and smokers in the age group of 20-25 years (P-value 0.001) and students of higher level of the study (P-value 0.005). About two-thirds (65.3%) of smokers began cigarette smoking after joining the College and 79.4% smoked 1 to 10 cigarettes per day. The association between number of cigarettes smoked per day and the duration of cigarette smoking in years showed statistically significant result (P. value 0.002). Conclusion: The daily cigarette smoking prevalence is still higher among undergraduate medical students. The higher prevalence of cigarette smoking might predict future adverse effects on health. This necessitates introduction of public health preventive and cessation programs which should be implemented by health and education authorities.